Carbonate apatite-coated material and its manufacturing method

The carbonate apatite coating material, featuring a rough support and a high carbonate group content apatite layer, addresses the limitations of existing materials by achieving both high carbonate content and strong adhesion, thereby improving clinical performance.

JP7665186B2Active Publication Date: 2025-04-21石川邦夫
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021056520
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-30
Publication Date
2025-04-21
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Existing carbonate apatite coating materials fail to simultaneously achieve high carbonate group content in the apatite structure and strong adhesion strength between the apatite layer and the support, which are essential for clinical applications.

Method used

A carbonate apatite coating material with a support having an arithmetic average surface roughness of 1.0 μm or more and a carbonate apatite layer with a chemically synthesized carbonate group content of 1 mass% or more, satisfying at least one of the conditions: (A) 5% carbonate group content and 10 MPa adhesion strength, (B) specific product value of carbonate group content and adhesion strength, or (C) embedded and covered carbonate apatite layer.

Benefits of technology

The proposed carbonate apatite coating material effectively meets the requirements of high carbonate group content and strong adhesion strength, enhancing its clinical utility and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665186000001
    Figure 0007665186000001
  • Figure 0007665186000002
    Figure 0007665186000002
  • Figure 0007665186000003
    Figure 0007665186000003
Patent Text Reader

Abstract

To provide an apatite carbonate covering material capable of highly satisfying both requirements of the following (1) and (2), where (1) the amount of carbonic acid group in an apatite structure is large, and (2) an adhesive strength between an apatite carbonate layer and a support is large.SOLUTION: An apatite carbonate covering material is manufactured in a manufacturing process including steps of: covering at least a part of a support having 1 μm or more of the arithmetic average surface roughness (Ra) of the surface with the precursor of apatite carbonate; and applying at least one component selected from a group of a phosphoric acid component, a calcium component and a carbonate component to the precursor by applying a solution including the component to the support having at least the part covered with the precursor of apatite carbonate to convert the precursor into apatite carbonate.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbonate apatite-coated material in which a support is at least partially coated with carbonate apatite, which exhibits excellent tissue affinity, osteoconductivity and bone replacement properties with biological tissues, and adsorbs proteins, bacteria, etc., and to a method for producing the same. [Background technology]

[0002] Carbonate apatite, which contains carbonate groups in the apatite structure, is useful as a medical material or adsorption material, but since it is a brittle material, carbonate apatite-coated materials, in which carbonate apatite is coated on a support, are sometimes used. Carbonate apatite-coated materials are expected to highly satisfy both of the following requirements (1) and (2). (1) The apatite structure contains a large amount of carbonate groups. (2) The adhesive strength between the carbonate apatite layer and the support is high. However, to date, there has been no carbonate apatite coating material that satisfies both requirements (1) and (2) to a high degree. Apatite also includes hydroxyapatite, which does not contain carbonate groups in the apatite structure. Hydroxyapatite-coated materials are produced by plasma spraying (Patent Document 1), flame spraying, baking, spraying-hydrothermal treatment (Patent Document 2), sputtering, and other methods. However, carbonate apatite is thermally decomposed at high temperatures, so carbonate apatite-coated materials could not be produced by these methods. In order to solve these problems, Patent Document 3 proposes a method for producing a carbonate apatite-coated material using a supersaturated solution. This method utilizes the crystal growth of carbonate apatite. That is, a support having nuclei from which carbonate apatite crystals will grow is immersed in an aqueous solution that is supersaturated with respect to carbonate apatite, and carbonate apatite crystals are grown from the nuclei to produce a carbonate apatite-coated material. The proposal in Patent Document 3 is an excellent manufacturing method for producing a carbonate apatite-coated material. However, the amount of carbonate groups in the apatite structure is 3 mass% or less, and the adhesive strength between the carbonate apatite layer and the support is about 3 to 5 MPa, which is not sufficient from a clinical standpoint.

[0003] When a carbonate apatite-coated material is used as a medical material such as an implant material, not only tissue binding but also pharmacological functions such as infection prevention may be required. Patent Document 4 proposes an implant material that is effective in preventing infection by forming a thermal spray coating made of a calcium phosphate-based material on the surface of a support and setting the silver concentration in the thermal spray coating to 0.02% by mass to 3% by mass. However, because the raw material is exposed to high temperatures during thermal spraying, carbonate apatite-coated materials cannot be produced, and silver cannot be introduced into the crystal structure of hydroxyapatite. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 62-34559 [Patent Document 2] Japanese Patent Application Publication No. 4-371146 [Patent Document 3] Japanese Patent Application Publication No. 2-255515 [Patent Document 4] JP 2012-40194 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, there has been no carbonate apatite-coated material that satisfies both the requirements (1) and (2) to a high degree. The present invention provides a carbonate apatite-coated material that satisfies both the requirements (1) and (2) to a high degree, and that also exhibits pharmacological functions, as well as a method for producing the same. [Means for solving the problem]

[0006] As a result of extensive investigations, the present inventors have found that a carbonate apatite-coated material comprising a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass % or more covering at least a part of the support, and which satisfies at least one condition selected from the group consisting of (A) to (C) below, is a carbonate apatite-coated material that satisfies both requirements (1) and (2) to a high degree, and further found a method for producing said carbonate apatite-coated material, thereby completing the present invention, except for carbonate apatite-coated materials in which the support is a ceramic material on whose surface carbonate apatite is formed when immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates. (A) The carbonate group content in the apatite structure is 5% by mass or more, and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is 10 MPa or more. (B) The product of the square of the mass percentage of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is 60%. 2 ·MPa or more. (C) At least a portion of the carbonate apatite layer is embedded in the surface of the support, and at least a portion of the embedded carbonate apatite layer is covered by the support.

[0007] That is, the present invention is as follows. (Hereinafter, the following inventions [1] to [6] may be referred to as inventions [1] to [6].) [1] A carbonate apatite-coated material comprising a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more, and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass% or more, which covers at least a part of the support, A carbonate apatite-coated material that satisfies at least one of the conditions selected from the group consisting of (A) to (C) below (however, this does not include carbonate apatite-coated materials whose support is a ceramic material on whose surface carbonate apatite is formed when immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates). (A) The carbonate group content in the apatite structure is 5% by mass or more, and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is 10 MPa or more. (B) The product of the square of the mass percentage of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is 60%. 2 ·MPa or more. (C) At least a portion of the carbonate apatite layer is embedded in the surface of the support, and at least a portion of the embedded carbonate apatite layer is covered by the support. [2] The carbonate apatite-coated material according to [1], characterized in that the support contains at least one of a material selected from the following group (D) or a polymer or copolymer of a compound selected from the following group (E). (D) Titanium, titanium alloys, stainless steel, cobalt chromium alloys, magnesium alloys, tantalum, polyether ether ketone, polyether ketone, polyarylate, polycarbonate, polyester, polyethylene terephthalate, glass, hydroxyapatite, alumina, zirconia (E) Lactic acid, glycolic acid, ε-caprolactone, glycerol, sebacic acid, hydroxybutyric acid, dioxanone [3] The carbonate apatite coating material according to any one of [1] and [2], which contains a drug in the carbonate apatite layer. [4] A method for producing a carbonate apatite-coated material (excluding carbonate apatite-coated materials in which the support is a ceramic material on the surface of which carbonate apatite is formed when the support is immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates) comprising a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass % or more covering at least a portion of the support, the method comprising both of the following steps (F) and (G): (F) A step of coating at least a portion of a support having an arithmetic mean surface roughness (Ra) of 1 μm or more with a carbonate apatite precursor. (G) A step of applying a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component to a support at least a portion of which is coated with a carbonate apatite precursor, thereby applying the component to the precursor and converting the precursor into carbonate apatite. [5] A method for producing a carbonate apatite-coated material according to [4], comprising at least one of the following steps (H) to (K): (H) applying to the support a solution containing calcium nitrate as an essential component and silver nitrate as an optional component; The nitrate on the surface of the support is thermally decomposed in a gas containing carbon dioxide to produce a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material, or the nitrate is thermally decomposed to produce a calcium oxide-coated material or a silver oxide-containing calcium oxide-coated material, and carbon dioxide is added to produce a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material; A step of applying a solution containing a phosphoric acid component to the calcium carbonate-coated material or the silver oxide-containing calcium carbonate-coated material to produce a carbonate apatite-coated material, or a silver oxide-containing carbonate apatite-coated material, or a silver phosphate-containing calcium carbonate-coated material. (I) applying a solution containing calcium carboxylate as an essential component and silver nitrate as an optional component to a support; Pyrolyzing the compound on the support surface to produce a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material; A step of applying a solution containing a phosphoric acid component to the calcium carbonate-coated material or the silver oxide-containing calcium carbonate-coated material to produce a carbonate apatite-coated material, or a silver oxide-containing carbonate apatite-coated material, or a silver phosphate-containing calcium carbonate-coated material. (J) A process for producing a carbonate apatite-coated material by embedding at least one selected from the group consisting of calcium carbonate, tricalcium phosphate, and tetracalcium phosphate into the surface of a support, and applying a solution containing at least a phosphoric acid component in the case of calcium carbonate, or applying a solution containing at least a carbonate component in the case of tricalcium phosphate and tetracalcium phosphate. (K) exposing the carbonate apatite coated material to a solution containing silver ions to produce a silver phosphate coated carbonate apatite coated material. [6] After the surface of the polymeric support is softened, dissolved, or melted, A step of pressing either carbonate apatite or carbonate apatite carrying a drug onto a surface of a support; and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass% or more covering at least a portion of the support, or a carbonate apatite layer carrying a drug. Effect of the Invention

[0008] The carbonate apatite-coated material of the present invention satisfies both the above requirements (1) and (2) to a high degree, and is highly useful, together with its production method. [Brief description of the drawings]

[0009] [Figure 1] Electron microscope (SEM) photographs of (a) titanium support (rough-surfaced titanium), (b) calcium carbonate-coated titanium, and (c) carbonate apatite-coated titanium (Example 1). [Diagram 2] 1 is a photograph showing a peeling test between carbonate apatite-coated titanium and bone (Example 1). [Diagram 3] FIG. 1 shows histopathological photographs by Villanueva-Goldner staining of (a) titanium support (rough-surface titanium), (b) calcium carbonate-coated titanium, and (c) carbonate apatite-coated titanium, all of which were embedded in rabbit tibias for 4 weeks (Example 1). [Figure 4] Electron microscope (SEM) photographs of (a) a polylactic acid plate, (b) a polylactic acid support (rough-surface polylactic acid), and (c) carbonate apatite-coated polylactic acid (Example 7). [Diagram 5] Electron microscope (SEM) photographs of (a) glass support (roughened glass), (b) calcium carbonate-coated glass, and (b) carbonate apatite-coated glass (Example 9). [Figure 6] 1 is an electron microscope photograph (SEM photograph) of carbonate apatite-coated polylactic acid (Example 10). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The configuration of the present invention will be described below. [1. Carbonate apatite-coated material of the present invention] <Essential requirements> The carbonate apatite-coated material of the present invention is a carbonate apatite-coated material comprising: a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more; and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass % or more covering at least a portion of the support.

[0011] <Presumed mechanism for producing the carbonate apatite-coated material of the present invention> The mechanism by which the carbonate apatite-coated material of the present invention, which satisfies both the requirements (1) and (2) to a high degree, is produced has not been fully elucidated. Furthermore, the present invention is not limited by the presumed mechanism. The present description is a presumption of the mechanism by which the carbonate apatite-coated material of the present invention is produced based on current knowledge. In the present invention, a carbonate apatite-coated material may be produced by converting a carbonate apatite precursor coated on the surface of a support into carbonate apatite through a dissolution-precipitation reaction. This dissolution-precipitation reaction will be described using an example where the precursor is calcium carbonate. The components of carbonate apatite are calcium, phosphoric acid, and carbonic acid, and the components of calcium carbonate are calcium and carbonic acid. Phosphoric acid, which is a component of carbonate apatite, is not contained in calcium carbonate. In order to convert calcium carbonate into carbonate apatite, a solution containing a phosphoric acid component, for example, a disodium hydrogen phosphate aqueous solution, is applied to a support coated with calcium carbonate. Specifically, for example, a support coated with calcium carbonate is immersed in a disodium hydrogen phosphate aqueous solution. Since the disodium hydrogen phosphate aqueous solution is unsaturated with respect to calcium carbonate, calcium carbonate dissolves in the disodium hydrogen phosphate aqueous solution, and calcium ions and carbonate ions are liberated. Since the disodium hydrogen phosphate aqueous solution contains phosphate ions, an environment in which calcium ions, carbonate ions, and phosphate ions coexist is created. This aqueous solution is supersaturated with respect to carbonate apatite, and carbonate apatite crystals are precipitated on the surface of calcium carbonate. These dissolution reactions and precipitation reactions occur continuously, and calcium carbonate is converted into carbonate apatite. In the compositional conversion of the precursor to carbonate apatite by the dissolution-precipitation reaction, a dissolution reaction is essential. Therefore, the precursor is basically peeled off from the support surface. In fact, in the case of a smooth support without unevenness, the precursor is peeled off from the support and a carbonate apatite-coated material is not produced. However, when the surface of the support is uneven, the precursor is not peeled off from the support, but rather a carbonate apatite-coated material is produced in which the precursor and the support are bonded with extremely high adhesive strength.

[0012] In order to increase the adhesive strength between the support and the carbonate apatite coating layer, at least two conditions must be satisfied. One is that the mechanical strength of the carbonate apatite layer must be high. The other is that the adhesive strength between the support and the carbonate apatite coating layer must be high. The carbonate apatite-coated material of the present invention is considered to satisfy these two conditions. In addition, both of these are considered to be unique phenomena in the dissolution-precipitation reaction using a precursor. That is, in the dissolution-precipitation reaction using a precursor, in order to convert the precursor into carbonate apatite, the precursor is immersed in a solution containing necessary components, and the components are added to the precursor. At this time, the precursor expands in volume, and a large interlocking force is generated between the carbonate apatite and the recesses of the support. From the viewpoint of the interlocking force, the unevenness of the support surface is an important factor, and it is essential that the arithmetic mean surface roughness (Ra) of the support surface is 1.0 μm or more. The mechanism by which a carbonate apatite layer with a high carbonate content can be produced by the present invention has not been fully elucidated. However, one of the reasons is thought to be that there is no need to use a solution that is supersaturated with respect to carbonate apatite. When a carbonate apatite layer is precipitated on a support surface from a supersaturated solution, the supersaturated solution is in equilibrium with the atmosphere, etc., so there is a limit to the amount of carbonate groups in the apatite structure of the carbonate apatite layer that can be produced. In the present invention, it is not necessary to use a saturated solution, and equilibrium with the atmosphere is not a concern. Whether the precursor contains a carbonate group component or the solution contains a carbonate group component, it is possible to use a raw material with a large carbonate group content, so it is believed that carbonate apatite with a large carbonate group content in the apatite structure can be produced.

[0013] <Carbonated apatite layer> In the present invention, carbonate apatite is defined as apatite containing carbonate groups. The basic structure of carbonate apatite is Ca 10-a (PO4) 6-b (CO3) c (OH) d (a, b, c, d are indefinite), and in addition to this basic structure, it may contain Na, K, Mg, HPO4, voids, etc. Carbonate apatite, for example, as described in Patent No. 4854300, is a 10 It can also be considered as an apatite in which some or all of the phosphate or hydroxyl groups of hydroxyapatite, which has the basic structure of (PO4)6(OH)2, have been replaced with carbonate groups. It is also an essential condition of the present invention that the carbonate apatite is chemically synthesized. Materials in which a support is coated with non-chemically synthesized carbonate apatite, such as natural bone, are not included in the present invention. Carbonate apatite produced using a chemically synthesized material as a precursor is chemically synthesized carbonate apatite. The carbonate apatite must cover at least a part of the support. If the carbonate apatite covers a part of the support, the function of the carbonate apatite is exhibited, but the greater the ratio of the carbonate apatite layer covering the support, the greater the function of the carbonate apatite. Therefore, the coverage is preferably 30% or more, more preferably 60% or more, and even more preferably 90% or more. 100% is ideal. The essential difference between carbonate apatite and hydroxyapatite is the presence or absence of carbonate groups in the apatite structure. The more carbonate groups there are in the apatite structure, the more susceptible it is to absorption by osteoclasts. When osteoclasts are activated, osteoblasts are activated through intercellular signaling, and new bone formation becomes vigorous. As a result, carbonate apatite is easily replaced by bone through bone remodeling. Furthermore, if there are many carbonate groups in the apatite structure, the apatite crystallites become smaller and the adsorptive activity increases. Although carbonate apatite is useful even if the carbonate group content in the apatite structure is less than 1% by mass, the effect of the carbonate group is relatively small. Therefore, in the present invention, it is essential that the carbonate group content is 1% by mass or more. Since a larger carbonate group content has a larger effect on the resorption activity by osteoclasts and on the crystallite size, the carbonate group content is preferably 3% by mass or more, and more preferably 5% by mass or more. Since the carbonate group content in the apatite structure of adult bone is 6 to 9% by mass, 6% by mass or more is more preferable, and 8% by mass or more is particularly preferable.

[0014] <Support> The support is a material that supports the carbonate apatite layer. Carbonate apatite exhibits useful properties such as tissue affinity, osteoconductivity, and adsorption, but is a brittle material. Therefore, in order to apply carbonate apatite to a site where stress is applied, it may be necessary to coat a support with excellent mechanical properties with carbonate apatite. Ceramic materials on the surface of which carbonate apatite is formed when immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts and carbonates cannot be used as supports. The support has a higher solubility in solution than carbonate apatite, and therefore cannot be expected to have the mechanical strength to support a carbonate apatite layer in vivo, which is one of the reasons why the ceramic material cannot be used as a support. For example, when a calcium carbonate block is immersed in a phosphate, the surface is converted to carbonate apatite, producing a carbonate apatite-coated calcium carbonate block. Therefore, the calcium carbonate block cannot be used as a support. In addition, the carbonate apatite-coated calcium carbonate block is a carbonate apatite-coated material that is not included in the present invention. When immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates, metals, polymers, ceramics, and composite materials thereof other than ceramic materials that form carbonate apatite on the surface can be used as the support without any restrictions.

[0015] <Arithmetic mean surface roughness (Ra) of the support surface> In the present invention, it is also an essential requirement that the support surface has an arithmetic mean surface roughness (Ra) of 1.0 μm or more. The arithmetic mean surface roughness (Ra) in the present invention is the arithmetic mean surface roughness specified in ISO25178. If the values ​​of Ra do not match between the measuring devices, the measurement value using the shape measuring laser microscope is used, and if there is also no agreement between the devices, the measurement value using a shape measuring laser microscope (VK-9710K) manufactured by Keyence Corporation is used as Ra. The carbonate apatite-coated material of the present invention can be produced by applying a solution to a material coated with a carbonate apatite precursor (hereinafter sometimes referred to as the precursor-coated material) and converting the precursor into carbonate apatite by a dissolution-precipitation method. As described in the assumed mechanism for producing the carbonate apatite-coated material of the present invention, the adhesive strength between the carbonate apatite layer and the support is the interlocking force between the recesses of the support and the carbonate apatite layer. Therefore, the unevenness of the support surface is an important factor, and it is essential that the arithmetic mean surface roughness (Ra) of the support surface is 1.0 μm or more. From the viewpoint of increasing the interlocking force, the arithmetic mean surface roughness (Ra) of the support surface is preferably 1.3 μm or more, more preferably 1.6 μm or more, and even more preferably 2.0 μm or more. The arithmetic mean surface roughness (Ra) of the support surface of the carbonate apatite-coated material is defined as the arithmetic mean surface roughness (Ra) of the support surface when the carbonate apatite is removed from the carbonate apatite-coated material. Carbonate apatite has a high solubility in acidic solutions. Therefore, the carbonate apatite layer can be easily dissolved and removed by using an acidic solution.

[0016] <Selection criteria> The carbonate apatite-coated material of the present invention must satisfy the above-mentioned essential conditions and at least one condition selected from the group of (A) to (C) above. The above (A) relates to a carbonate apatite coating material having a relatively large carbonate group content in the apatite structure. The carbonate group content in the apatite structure is more preferably 6 mass % or more, and further preferably 8 mass % or more. On the other hand, if the adhesive strength between the support and the apatite layer is low, the carbonate apatite layer will peel off from the support. Therefore, the adhesive strength needs to be 10 MPa or more. The adhesive strength is preferably 20 MPa or more, more preferably 40 MPa or more, and even more preferably 60 MPa or more. The above (B) relates to a carbonate apatite coating material having a relatively low carbonate content, for example, 1% by mass or more and less than 5% by mass in the apatite structure. When the carbonate content is low, osteoclast resorption slows down, and bone remodeling also slows down. Therefore, a high adhesive strength is required between the carbonate apatite coating layer and the support. Under these conditions, the product of the square of the mass percentage of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is 60%. 2 · MPa or more, but 100% 2 ·MPa or more is preferable, 300% 2 ·MPa or more is more preferable, 600% 2 ·MPa or more is even more preferable. The above condition (C) relates to cases where the support is plastically deformed, dissolved, or melted. By embedding at least a part of the carbonate apatite layer in the surface of the support, a large adhesive force acts between the support and the carbonate apatite layer. Furthermore, by covering at least a part of the embedded carbonate apatite layer with the support, the adhesive force between the support and the carbonate apatite layer becomes even greater, and sufficient clinical usefulness is demonstrated. When the condition of the above condition (C) is met, the carbonate apatite layer is adhered to the surface of the support by a fitting force, so the adhesive strength between the carbonate apatite layer and the surface of the support is large. Therefore, when the condition of the above condition (C) is met, the condition of the above condition (2) is met, and therefore there is no need to measure the adhesive strength between the carbonate apatite layer and the surface of the support.

[0017] <Adhesive strength between support and carbonate apatite coating layer> The adhesive strength between the support and the carbonate apatite layer in the present invention is measured in accordance with the adhesive strength test method for hydroxyapatite-coated materials described in ISO13779-4:2018-12, paragraph 4. In this standard, hydroxyapatite is to be read as carbonate apatite, and surgical implant is to be read as support. Basically, the adhesive strength is measured between the support and the carbonate apatite layer at the portion of the support that is covered with the carbonate apatite layer. If it is impossible to measure the portion of the support that is covered with the carbonate apatite layer, the adhesive strength between the support and the adhesive used for the measurement is subtracted by area fraction from the adhesive strength at that portion to define the adhesive strength between the support and the carbonate apatite layer. However, if the carbonate apatite coverage is 60% or more and the adhesive strength is 3 MPa or more, for simplicity, the adhesive strength at that portion is regarded as the adhesive strength between the support and the carbonate apatite coating layer.

[0018] <2. Preferred Support> As described above, metals, polymers, ceramics, and composite materials thereof can be used as the support for the carbonate apatite-coated material of the present invention, provided that the support is other than a ceramic material on which carbonate apatite is formed when immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates, and the arithmetic mean surface roughness (Ra) of the surface is 1.0 μm or more. Metals are suitable as supports because they have excellent mechanical properties and are useful for implants, stents, etc. Among metal materials, "titanium, titanium alloys, stainless steel, cobalt-chromium alloys, magnesium alloys, and tantalum" are preferred metal supports because they have excellent not only mechanical properties but also tissue reactions. When carbonate apatite-coated metal materials are used as implant materials, the carbonate apatite is replaced by new bone in harmony with bone remodeling, and the new bone bonds with the metal material. Therefore, metal materials with high tissue affinity are preferred materials as supports. Among "titanium, titanium alloys, stainless steel, cobalt-chromium alloys, magnesium alloys, and tantalum," titanium and titanium alloys are particularly preferred from the viewpoint of tissue affinity. Therefore, a carbonate apatite-coated material having a support that is titanium or a titanium alloy with an arithmetic mean surface roughness (Ra) of 1.0 μm or more and a chemically synthesized carbonate apatite layer that covers at least a part of the support and has a carbonate group content of 1 mass% or more, the carbonate group content in the apatite structure is 5 mass% or more, and the adhesive strength between the support and the carbonate apatite layer that covers at least a part of the support is 10 MPa or more is a particularly useful material. On the other hand, polymers have excellent properties such as an elastic modulus close to that of biological tissues and X-ray transparency. Among polymers, "polyether ether ketone, polyether ketone, polyarylate, polycarbonate, polyester, and polyethylene terephthalate" are preferred polymer supports because they are excellent not only in mechanical properties but also in tissue reaction. Furthermore, polymers or copolymers of the compounds selected from the group (E) have an excellent balance of mechanical properties, tissue reaction, and bioabsorbability. Carbonate apatite is replaced by new bone in harmony with bone remodeling, so when the support is a bioabsorbable polymer, it is an ideal material that has bone formation ability and is absorbed and replaced by bone, etc. Ceramic materials exhibit excellent properties such as not inducing allergies. Among ceramic materials, "glass, hydroxyapatite, alumina, and zirconia" are preferred ceramic supports because they not only do not induce allergies but also have excellent tissue reactions. In addition, some glasses have excellent transparency, so they are also preferred as materials for evaluating osteoclast activity.

[0019] <3 Drug-containing carbonate apatite-coated material> The carbonate apatite-coated material of the present invention has excellent osteoconductivity, and further functional improvements are expected by including drugs such as bone morphogenetic proteins. In addition, although the carbonate apatite-coated material of the present invention does not exhibit antibacterial properties, it is expected to be endowed with pharmacological functions by including antibacterial drugs such as silver. As described later, the carbonate apatite-coated material of the present invention is characterized in that a carbonate apatite-coated material containing a drug can be produced due to the production method and the properties of the carbonate apatite-coated layer formed. The type of drug contained in the carbonate apatite layer is not particularly limited. When the purpose is to bond the carbonate apatite coating material to bone or soft tissue, bone morphogenetic proteins, vascular endothelial growth factors, fibroblast growth factors, etc. are effective. When the purpose is to prevent infection, inorganic antibacterial agents such as silver, copper, and zinc, and organic antibacterial agents such as benzalkonium and hinokitiol are effective. Among drugs intended for preventing infection, silver is particularly useful because it exhibits antibacterial properties at low concentrations and is also incorporated into the carbonate apatite structure. From the viewpoint of the balance between infection prevention ability and tissue affinity, the silver concentration is preferably 0.02% to 3% by mass relative to the carbonate apatite, more preferably 0.05% to 2% by mass, and even more preferably 0.1% to 1% by mass.

[0020] <Specific uses of carbonate apatite-coated materials> The carbonate apatite-coated material of the present invention is not limited in its applications, and can be used in a wide range of applications, such as medical materials, catalyst carriers, and wastewater treatment. On the other hand, carbonate apatite is an inorganic composition of bone, and has excellent osteoconductivity and tissue affinity. Therefore, the carbonate apatite-coated material of the present invention is particularly useful as a medical material. The medical material referred to in the present invention is a material used in medical treatment or a material related to medical treatment, and examples of such materials include implant materials, spinal cages, stents, percutaneous terminals such as skin buttons, internal and external fixation devices, catheters, sustained drug release carriers, and materials for evaluating osteoclast activity.

[0021] <4. Manufacturing method of carbonate apatite-coated material> The present invention [4] is useful as a method for producing a carbonate apatite-coated material. In the above (F), the coating method is not particularly limited, and any known coating method can be used without limitation. When at least a part of a support having an arithmetic mean surface roughness (Ra) of less than 1 μm is coated with a carbonate apatite precursor by blasting or pressing, the arithmetic mean surface roughness (Ra) of the support is 1 μm or more as a result, the process is defined as including the step (F). This is because the step of producing a support having an arithmetic mean surface roughness (Ra) of 1 μm or more by blasting and the step of coating at least a part of the support with a carbonate apatite precursor are considered to be performed simultaneously. In the above (G), for example, the precursor of carbonate apatite coating the support is immersed in a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component, thereby converting the composition into carbonate apatite. A simple step of immersing the precursor coating material in the solution is convenient, but a step of spraying the solution onto the precursor coating material with a sprayer or the like may also be used. In the present invention, applying a solution includes various means such as immersion, spraying, and coating.

[0022] Preferred Precursors In the method for producing a carbonate apatite-coated material of the present invention, any compound that is converted into carbonate apatite when a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component is added can be used as a precursor without any restrictions, but "at least one selected from the group consisting of calcium carbonate, calcium hydroxide, calcium oxide, tetracalcium phosphate, tricalcium phosphate, octacalcium phosphate, calcium hydrogen phosphate, calcium sulfate, and zinc phosphate" is preferred as a carbonate apatite precursor. In the present invention, the precursor includes a precursor of a precursor (a precursor before a precursor) and a precursor before a precursor. For example, calcium hydroxide and calcium oxide are precursors of calcium carbonate, and when these are carbonated, calcium carbonate, which is a precursor of carbonated apatite, is produced. In the present invention, these are also defined as precursors. Calcium carbonate is a precursor containing a calcium component and a carbonate component, tetracalcium phosphate, tricalcium phosphate, octacalcium phosphate, and calcium hydrogen phosphate are precursors containing a phosphate component and a calcium component, calcium sulfate is a precursor containing a calcium component, and zinc phosphate is a precursor containing a phosphate component. These contain the composition necessary for the formation of carbonate apatite and have a solubility suitable for dissolution-precipitation reactions. Calcium hydroxide and calcium oxide are also useful as precursors containing a calcium component, but it is more preferable to carbonate them and use them as calcium carbonate. Of the carbonate apatite compositions consisting of calcium, carbonate and phosphate, those containing two components are more preferred. Calcium carbonate is also preferred for producing carbonate apatite with a high carbonate group content. In order to convert calcium hydroxide and calcium oxide into calcium carbonate, carbon dioxide may be added. This also causes volume expansion, so calcium hydroxide and calcium oxide are particularly preferred as precursors. The method for coating the support with the carbonate apatite precursor is not particularly limited, and any known coating method such as flame spraying, plasma spraying, blasting, dipping, painting, pyrolysis, carbonation, or a composition conversion method of the coating material can be used without limitation.

[0023] <Preferred steps in producing the precursor coating material> In the method for producing a carbonate apatite-coated material of the present invention, the above-mentioned (F) may be necessary. In this step, it is sufficient to coat at least a part of a support having an arithmetic mean surface roughness (Ra) of 1 μm or more with a carbonate apatite precursor, and any known step may be used without limitation, but a step selected from the following group is preferable for producing a precursor-coated material. (F-1) "A step including a step of blasting a support" is a step useful for roughening the surface of a support and producing a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more. As the blasting, any known blasting method can be used without any restrictions. In the blasting process, it is possible to simultaneously roughen the support and impart a carbonate apatite precursor to the support surface. For example, by blasting the support with tricalcium phosphate or calcium carbonate as a blasting medium, it is possible to form irregularities on the support surface and impart the carbonate apatite precursor, tricalcium phosphate or calcium carbonate, to the support surface. (F-2) "A process including an etching treatment on a support" is also a useful process for roughening the surface of the support and manufacturing a support having an arithmetic average surface roughness (Ra) of 1.0 μm or more. In some cases, it may be useful to perform an etching treatment after the blasting treatment. As the etching treatment, known etching methods such as acid etching and laser etching can be used without limitation. Among the etching treatments, acid etching is particularly preferred from the viewpoint of simplicity and efficient surface roughening. In acid etching, the support is immersed in an acid solution such as sulfuric acid, nitric acid, phosphoric acid, hydrochloric acid, and hydrofluoric acid. It is particularly useful to perform a blasting treatment to form a relatively large uneven structure, and then perform an etching treatment to form a relatively small uneven structure. (F-3) "A step including a step of heat treating the carbonate apatite precursor on the surface of the support" is useful for firmly binding the carbonate apatite precursor to the support, drying a solution containing the precursor, or thermally decomposing the precursor. For example, when an ethanol solution of calcium nitrate is applied to a titanium support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more, and the calcium nitrate is decomposed by heat treatment, a material can be produced in which calcium oxide, a precursor of calcium carbonate, which is a precursor of carbonate apatite, is firmly bound to the surface of the support. (F-4) "A step including a step of adding carbon dioxide to the carbonate apatite precursor on the surface of the support" is useful when the precursor of carbonate apatite is a compound that does not contain a carbonate group, such as calcium oxide or calcium hydroxide. The method of adding carbon dioxide is not particularly limited, and any known method of adding carbon dioxide can be used without limitation. For example, when calcium oxide is carbonated to form vaterite, calcium oxide may be exposed to carbon dioxide in a methanol atmosphere at 4°C. Calcium oxide, which is a precursor of carbonate apatite, is carbonated to form vaterite, which is a direct precursor of carbonate apatite. (F-5) "A step including a step of pressing a carbonate apatite precursor onto a support" is the simplest step among "steps of coating at least a part of a support with a carbonate apatite precursor". It is sufficient to simply press a precursor powder, precursor granules, precursor paste, or the like onto the support. The pressure for pressing is not particularly limited, but is preferably 0.1 MPa or more, more preferably 0.5 MPa or more, and even more preferably 1.0 MPa or more. In addition, the pressing method can be any known method without any restrictions, and examples thereof include uniaxial pressing and cold isostatic pressing. (F-6) "A process including a softening process, a dissolving process, or a melting process of the surface of a support made of a polymer material" is useful in a process of pressing a carbonate apatite precursor against a support made of a polymer material, or in a process of blasting a polymer support. When a softening process, a dissolving process, or a melting process is performed on the surface of a support made of a polymer material, the surface of the polymer material becomes soft. As a result, the support can be easily coated with the carbonate apatite precursor by the process of pressing a carbonate apatite precursor against a support made of a polymer material, or by the process of blasting a polymer support.

[0024] <Method for producing drug-loaded carbonate apatite-coated material> The carbonate apatite-coated material of the present invention is produced by converting the precursor of the precursor-coated material into carbonate apatite by dissolution-precipitation. Therefore, a carbonate apatite-coated material containing a drug can be easily produced by adding a drug at the stage of producing the precursor or by adding a drug to the solution applied to the precursor-coated material. In addition, since the carbonate apatite produced by the present invention has micropores, the carbonate apatite layer is impregnated with a drug by contacting the carbonate apatite-coated material with a drug solution, so that a carbonate apatite-coated material containing a drug can be easily produced. Furthermore, carbonate apatite has a larger crystal distortion than hydroxyapatite, and is characterized in that metals can be contained not only between crystals but also within the crystal structure. Due to these characteristics, compared with other calcium phosphate-coated materials, the carbonate apatite-coated material of the present invention can be easily produced as a carbonate apatite-coated material containing a drug. By utilizing these unique methods for producing carbonate apatite-coated materials, carbonate apatite-coated materials carrying drugs can be produced. There is no limitation on the method for producing a carbonate apatite-coated material carrying a drug. However, a method for producing a carbonate apatite-coated material containing a drug in the carbonate apatite layer that includes at least one step selected from the group consisting of the following steps is useful: "A process including a step of coating a support with a carbonate apatite precursor mixed with a drug" is a method of supporting a drug at the precursor stage. It is possible to support a large amount of drug relatively easily. The precursor is converted into carbonate apatite by a dissolution-precipitation reaction, during which time some of the drug is released into the solution, but the drug is also supported in the carbonate apatite layer that is formed. "A process including a step of mixing a drug into a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component, which is applied to a carbonate apatite precursor coating material" is a method in which, for example, when a precursor coating material is immersed in a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component, the drug is mixed into the solution, thereby causing the drug to be supported on the carbonate apatite, and has the characteristic that the drug can be supported relatively uniformly on the carbonate apatite layer. "A process including a process of impregnating a carbonate apatite-coated material with a solution containing a drug" is a method for efficiently supporting a drug in a carbonate apatite layer. This process is possible because the carbonate apatite layer has micropores. In order to increase the amount of drug supported in the micropores in the carbonate apatite layer or to facilitate drug support, the process of impregnating a carbonate apatite-coated material in a reduced pressure state with a solution containing a drug is a more useful process.

[0025] <5. Particularly useful method for producing carbonate apatite-coated material> It is particularly useful for the method for producing a carbonate apatite-coated material to include any one of the steps (H) to (K). The above (H) is basically a process of producing a calcium carbonate-coated material, which is a precursor of carbonate apatite, from calcium nitrate, which is a precursor of calcium carbonate, and converting the composition of calcium carbonate to carbonate apatite by immersing in an aqueous solution containing a phosphoric acid component, thereby producing a carbonate apatite-coated material. Basically, the calcium nitrate on the surface of the support is thermally decomposed in a gas containing sufficient carbon dioxide to produce a calcium carbonate-coated material. From the viewpoint of the purity and formation rate of calcium carbonate formed, the carbon dioxide concentration in the gas is preferably 10% by volume or more, more preferably 30% by volume or more, and even more preferably 50% by volume or more. Since calcium nitrate is thermally decomposed at about 500°C to 600°C, the heat treatment is performed at a temperature above this temperature and below 920°C, which is the thermal decomposition temperature of calcium carbonate. Within this temperature range, a calcite-coated material can be produced, but in order to convert the composition of calcium carbonate to carbonate apatite by immersing it in a solution, a lower heat treatment temperature is preferable. On the other hand, when the calcium oxide-coated material is thermally decomposed in a gas that does not contain sufficient carbon dioxide, a calcium oxide-coated material is produced. When carbon dioxide is added to the produced calcium oxide-coated material, a calcium carbonate-coated material is produced. Also, when the calcium oxide-coated material is exposed to carbon dioxide, calcite formation is suppressed, thereby producing a vaterite-coated material. There are no particular limitations on the method for suppressing calcite formation, but for example, a method in which the calcium oxide-coated material is exposed to carbon dioxide in an atmosphere of 90% by volume methanol or 90% by volume ethanol (other than the listed components is water) is useful because calcite formation is efficiently suppressed and vaterite is formed. Vaterite is a metastable phase, and is therefore more reactive than calcite. A carbonate apatite-coated material is produced by applying a solution containing a phosphoric acid component to the calcium carbonate-coated material, for example by immersing the calcium carbonate-coated material in an aqueous solution containing a phosphoric acid component. When the calcium nitrate on the support surface contains silver nitrate, silver oxide is formed by thermal decomposition, and a carbonate apatite-coated material containing silver oxide, a type of drug, is produced. A certain amount of silver is incorporated into the carbonate apatite structure, so a highly functional carbonate apatite-coated material containing silver oxide can be produced. The above (I) is a manufacturing method using calcium carboxylate instead of calcium nitrate. Since calcium carboxylate becomes calcium carbonate by thermal decomposition, a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material is produced. By adding a solution containing a phosphoric acid component to the coating material, a carbonate apatite-coated material or a silver oxide-containing carbonate apatite-coated material is produced. In the above (J), first, at least one selected from the group consisting of calcium carbonate, tricalcium phosphate, and tetracalcium phosphate, which are precursors of carbonate apatite, is embedded in a support. The embedding method in the support is not particularly limited, and a known embedding method can be used. For example, at least one selected from the group consisting of calcium carbonate, tricalcium phosphate, and tetracalcium phosphate may be used as a blasting medium to blast the support, thereby embedding at least one selected from the group consisting of calcium carbonate, tricalcium phosphate, and tetracalcium phosphate in the support. Alternatively, a recess may be formed in the support, and then at least one selected from the group consisting of calcium carbonate, tricalcium phosphate, and tetracalcium phosphate may be provided in the recess. Next, in the case of calcium carbonate, a solution containing a phosphoric acid component is applied to convert the calcium carbonate into carbonate apatite. In the case of tricalcium phosphate or tetracalcium phosphate, a solution containing a carbonate component is applied to convert the tricalcium phosphate or tetracalcium phosphate into carbonate apatite. In the case of tricalcium phosphate or tetracalcium phosphate, if a solution containing only a carbonate component is applied, the composition may be converted into calcium carbonate rather than carbonate apatite. In the case of tricalcium phosphate or tetracalcium phosphate, it is also effective to apply a solution containing both a carbonate component and a phosphoric acid component. The above (K) is a manufacturing process for a carbonate apatite-coated material coated with silver phosphate. When the carbonate apatite-coated material is exposed to a solution containing silver ions, the carbonate apatite surface is converted to silver phosphate through a dissolution-precipitation reaction. By coating the surface of the carbonate apatite layer that is firmly attached to the support with silver phosphate, it is possible to impart silver components that exhibit pharmacological effects such as antibacterial properties to the carbonate apatite layer.

[0026] <6. Manufacturing method of carbonate apatite-coated polymer material> Of the support materials, polymer materials are characterized by being easily softened, dissolved, or melted. Therefore, a carbonate apatite-coated material that satisfies at least the above condition (C), comprising a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more and a chemically synthesized carbonate apatite layer with a carbonate group content of 1 mass% or more covering at least a portion of the support, or a carbonate apatite layer carrying a drug, can be produced by softening, dissolving, or melting the surface of a polymer support and then pressing either carbonate apatite or carbonate apatite carrying a drug onto the surface of the support. The volume of one selected from the group consisting of carbonate apatite precursor, carbonate apatite, drug-loaded carbonate apatite precursor, and drug-loaded carbonate apatite to be pressed is 5×10 -16 m 3 It is preferable that the number is equal to or larger than 1×10 -13 m 3 More preferably, it is 1×10 -12 m 3 More preferably, it is equal to or greater than this. EXAMPLES

[0027] The present invention will be described in more detail below using examples, but the scope of the present invention is not limited to these examples. The general conditions are as follows. Any deviations from these conditions are noted in the individual Examples or Comparative Examples.

[0028] (Titanium plate) Two types of medical grade titanium (manufactured by T&I Co., Ltd.) were used. The arithmetic surface roughness (Ra) was 0.7±0.1μm. (Glass plate) The slide glass used was made of soda glass. The arithmetic surface roughness (Ra) was 0.02±0.004μm. (Polylactic acid plate) Polylactic acid (NatureWorks, 3251D) was melted at 200°C, molded into a disk shape, and then heat-treated at 150°C for 24 hours to prepare a polylactic acid plate. The arithmetic surface roughness (Ra) was 0.3±0.2 μm. (Polyetheretherketone plate) Polyetheretherketone (PEEK450) manufactured by Victrex was used. The arithmetic surface roughness (Ra) was 0.6±0.2 μm. (Electric furnace) The furnace used was MINI-1 manufactured by Nitto Kagaku Co., Ltd. The size of the furnace interior was 7cm x 5cm x 12cm. (Powder X-ray diffraction analysis: XRD analysis) XRD analysis was performed using a BRUKER D8 ADVANCE type powder X-ray diffractometer. The output was 40 kV, 40 mA, and the X-ray source was CuKα (λ=0.15418 nm). The pattern obtained by XRD analysis is called the XRD pattern. (Fourier transform infrared spectrophotometric analysis: FT-IR analysis) FT-IR analysis was performed using a JASCO FT / IR-6200. (Carbonated Content Analysis) Carbonate content analysis was performed by measuring the carbon content using a Yanaco Technical Science Co., Ltd. carbon, hydrogen, and nitrogen simultaneous quantitative analyzer, CHN Coder (MT-6), and the carbon content was multiplied by 5 to determine the carbonate content. (arithmetic mean surface roughness) In the present invention, the arithmetic mean surface roughness (Ra) of the support surface was measured using a shape measuring laser microscope (VK-9710K) manufactured by Keyence Corp. In the present invention, the arithmetic mean surface roughness (Ra) is the arithmetic mean surface roughness (Ra) measured using a shape measuring laser microscope. (Adhesive strength) The adhesive strength was measured using a Shimadzu universal testing machine (AGS-J type) in accordance with ISO13997-4:2018-12, paragraph 4. The adhesive used was Araldite 2011 manufactured by HUNTSMAN. If a different value was obtained in the adhesive strength measurement, the measurement result using that adhesive is regarded as the adhesive strength of the present invention. (Drugs) The chemicals used in the present examples and comparative examples were all of special grade reagents, and therefore all the carbonate apatite-coated materials produced were chemically synthesized carbonate apatite-coated materials. (Notation) In the drawings of the examples, titanium may be written as Ti, polylactic acid as PLA, calcium carbonate as CaCO3, and carbonate apatite as CO3Ap.

[0029] [Example 1] <Production process of rough surface support> The titanium plate was immersed in a mixed acid solution containing 50% by volume of sulfuric acid and 7% by volume of hydrochloric acid at 70°C for 30 minutes for acid etching, and then washed with distilled water. The arithmetic surface roughness (Ra) of the produced roughened titanium was 2.2±0.7μm. An SEM image of the roughened titanium is shown in Figure 1(a). <Precursor coating process> The roughened titanium was then coated with 8 μL / cm of a 99.5% by volume ethanol solution of calcium nitrate tetrahydrate at a concentration of 0.5 molar. 2 The coating was applied so as to obtain a coating composition having a thickness of 100 mm or less, and the coating composition was heated to 550° C. at 3° C. per minute in an electric furnace under a carbon dioxide gas flow of 100 mL per minute. After heat treatment at 550° C. for 5 hours, the coating composition was cooled in the furnace. XRD analysis revealed that calcite was formed on the roughened titanium surface. An SEM image of the calcite-coated titanium is shown in Figure 1(b). The adhesive strength between the calcite layer and the roughened titanium substrate was 56.6±16.1MPa, and the main fracture mode was between the roughened titanium and the calcite layer, with fracture within the calcite layer also observed. <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting calcite into carbonate apatite, the calcite-coated titanium was immersed in a 0.2 molar Na2HPO4 aqueous solution at 80°C for 7 days. XRD, FT-IR and elemental analysis showed that calcite was converted to carbonate apatite. The carbonate group content of carbonate apatite was 9.6% by mass. SEM image of carbonate apatite-coated titanium is shown in Figure 1(c). The carbonate apatite coverage was 100%, and the adhesive strength between carbonate apatite and the roughened titanium substrate was 76.8±2.7MPa. The fracture mode was mainly between the roughened titanium and the carbonate apatite layer, and fracture within the carbonate apatite layer was also observed. The carbonate apatite was dissolved in a 1 mol / L nitric acid aqueous solution, and the arithmetic surface roughness (Ra) of the roughened titanium substrate was measured to be 2.1±0.6μm. It was found that the arithmetic surface roughness (Ra) of the roughened titanium substrate was essentially the same even after the precursor coating process and the deficient component addition process were performed. From these results, it is considered that the carbonate apatite coating material has a carbonate group content of 5 mass% or more in the apatite structure and an adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 77 MPa, and the product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 7000%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced. To verify the usefulness of carbonate apatite-coated titanium as a medical material, roughened titanium, calcite-coated titanium, and carbonate apatite-coated titanium, each 10 mm long, 10 mm wide, and 1 mm thick, were embedded in the tibiae of 12-week-old rabbits for 4 weeks, and a pull-off test was conducted (Fig. 2). The pull-off forces between the bone and the roughened titanium, calcite-coated titanium, and carbonate apatite-coated titanium were 8.2±4.6N, 24.4±10.7N, and 45.2±17.6N, respectively, and the carbonate apatite-coated titanium showed a significantly higher pull-off force than the roughened titanium and calcium carbonate titanium. Figure 3 shows Villanueva-Goldner stained images four weeks after implantation. The bone contact rates for the roughened titanium, calcite-coated titanium, and carbonate apatite-coated titanium were 48.2±7.8%, 59.9±15.4%, and 73.0±6.4%, respectively, with carbonate apatite-coated titanium showing a significantly higher bone contact rate than the roughened titanium and calcite-coated titanium. The bone contact rate of carbonate apatite-coated titanium was also higher than that of hydroxyapatite-coated titanium. These results demonstrate that carbonate apatite-coated materials are highly useful as medical materials.

[0030] [Example 2] <Precursor coating process> The roughened titanium produced in Example 1 was coated with 8 μL / cm of a 99.5% by volume ethanol solution of calcium nitrate tetrahydrate at a concentration of 0.5 molar. 2 The roughened titanium coated with calcium nitrate was heated in air at 3°C ​​per minute to 550°C using an electric furnace, heat-treated at 550°C for 5 hours, and then cooled in the furnace. XRD analysis showed that calcium oxide was formed on the roughened titanium surface. The calcium oxide-coated titanium was then exposed to carbon dioxide saturated with 90% by volume of methanol at 4°C for 24 hours. XRD analysis showed that the calcium oxide was converted to vaterite. <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting vaterite into carbonate apatite, the vaterite-coated roughened titanium was immersed in a 0.2 molar Na2HPO4 aqueous solution at 20°C for one day. XRD analysis, FT-IR analysis, and elemental analysis revealed that vaterite was converted to carbonate apatite. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 10.2 mass%. The adhesive strength between the carbonate apatite and the roughened titanium substrate was 52.4 ± 1.9 MPa, and the main fracture mode was between the roughened titanium and the carbonate apatite layer, with fracture within the carbonate apatite layer also observed. The carbonate apatite was dissolved in a 1 mol / L aqueous nitric acid solution, and the arithmetic surface roughness (Ra) of the roughened titanium substrate was measured to be 2.1 ± 0.7 μm, indicating that the arithmetic surface roughness (Ra) of the roughened titanium substrate was essentially the same even after the precursor coating process and the deficient component addition process were performed. From these results, it is considered that the carbonate apatite coating material has a carbonate group content of 5 mass% or more in the apatite structure and an adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 52 MPa, and the product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 5500%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0031] [Example 3] The roughened titanium produced in Example 1 was applied with 5 μL / cm of a 99.5% by volume ethanol solution of 0.5 molar calcium acetate. 2 The roughened titanium coated with calcium acetate was heated to 380°C at 2°C per minute in an electric furnace in the atmosphere, heat-treated at 380°C for 5 hours, and then cooled in the furnace. XRD analysis revealed that calcite, a stable polymorph of calcium carbonate, was formed. In other words, it was found that calcium acetate was thermally decomposed on the roughened titanium surface to produce calcite-coated titanium. <Step of adding missing components> The same deficient component providing step as in Example 1 was carried out. As a result of XRD analysis and FT-IR analysis, it was found that calcium carbonate was converted into carbonate apatite. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 9.2 mass%. The adhesive strength between the carbonate apatite and the roughened titanium substrate was 57.2±3.1 MPa, and the main mode of destruction was between the roughened titanium and the carbonate apatite layer, with destruction within the carbonate apatite layer also being observed. The carbonate apatite was dissolved in a 1 molar nitric acid aqueous solution, and the arithmetic surface roughness (Ra) of the roughened titanium substrate was measured, which was 2.2±0.6 μm, and it was found that the arithmetic surface roughness (Ra) of the roughened titanium substrate was substantially the same even after the precursor coating step and the deficient component providing step were carried out. From these results, it is considered that the carbonate apatite coating material has a carbonate group content of 5 mass% or more in the apatite structure and an adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 57 MPa, and the product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 4800%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0032] [Example 4] <Rough surface support manufacturing process> The roughened titanium produced in Example 1 was sprayed with a mixed aqueous solution of 0.5 mol / L calcium nitrate and 1 mmol / L silver nitrate at 8 μL / cm 2 The roughened titanium was heated to 550°C at 3°C ​​per minute in an electric furnace under a carbon dioxide gas flow of 100 mL per minute, heat-treated at 550°C for 5 hours, and then cooled in the furnace. XRD analysis revealed that calcite, a stable polymorph of calcium carbonate, was formed on the surface of the roughened titanium. <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting calcite into carbonate apatite, the calcite-coated roughened titanium was immersed in a 0.2 molar Na2HPO4 aqueous solution at 80°C for 7 days. XRD analysis, FT-IR analysis, and elemental analysis revealed that calcite was converted to carbonate apatite. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 9.6 mass%. The adhesive strength between the carbonate apatite and the roughened titanium substrate was 75.6 ± 3.1 MPa, and the main fracture mode was between the roughened titanium and the carbonate apatite layer, with fracture within the carbonate apatite layer also observed. The carbonate apatite layer was dissolved in a 1 molar nitric acid solution at 60°C, and the arithmetic surface roughness (Ra) of the roughened titanium substrate was measured to be 2.0 ± 0.8 μm, indicating that the arithmetic surface roughness (Ra) of the roughened titanium substrate was essentially the same even after the precursor coating process and the deficient component addition process were performed. The silver concentration in the nitric acid solution in which the carbonate apatite layer was dissolved was quantitatively analyzed by ICP emission spectroscopy, and the silver concentration in the carbonate apatite layer was calculated to be approximately 0.2 mass% relative to the carbonate apatite. From these results, it is possible to determine that the carbonate apatite-coated material contains about 0.2% by mass of silver with respect to the carbonate apatite, has a carbonate group content of 5% by mass or more in the apatite structure, and has an adhesive strength of about 56 MPa between the support and the carbonate apatite layer that covers at least a part of the support, and that the product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer that covers at least a part of the support is about 7000%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0033] [Example 5] The carbonate apatite-coated material produced in Example 1 was impregnated with basic fibroblast growth factor manufactured by Kaken Pharmaceutical Co., Ltd. First, 15 μg of basic fibroblast growth factor and 1.5 μg of a fluorescent reagent (HiLyte Fluoro488) manufactured by Cosmo Bio Co., Ltd. were mixed to prepare 300 μL of an aqueous solution, and unreacted basic fibroblast growth factor and the fluorescent reagent were removed using a spin column with a molecular weight cutoff of 10K. At 0°C under reduced pressure, fluorescently labeled basic fibroblast growth factor was dropped onto the carbonate apatite-coated material so as to cover the entire surface of the coating, and then the pressure was returned to normal. Fluorescence microscopy of the cut surface of the carbonate apatite-coated material confirmed that the basic fibroblast growth factor had penetrated into the carbonate apatite layer. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 9.8% by mass. The adhesive strength between the carbonate apatite and the roughened titanium substrate was 73.4±3.2MPa, and the main fracture mode was between the roughened titanium and the carbonate apatite layer, with fracture within the carbonate apatite layer also observed. The carbonate apatite was dissolved in a 1 mol / L aqueous nitric acid solution, and the arithmetic surface roughness (Ra) of the roughened titanium substrate was measured to be 2.0±0.7μm. From these results, it was confirmed that a carbonate apatite-coated material containing a drug in the carbonate apatite layer was produced. The carbonate apatite-coated material has a carbonate group content of 5% by mass or more in the apatite structure, and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is about 73 MPa. The product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is about 7000%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0034] [Example 6] The carbonate apatite-coated material produced in Example 1 was used. <Silver phosphate coating process> Carbonate apatite-coated titanium was immersed in aqueous silver nitrate solutions of 0.01, 0.1, 1, and 10 millimolar concentrations at 25°C for 1 hour, washed with distilled water, and then dried. The silver concentration was measured by inductively coupled plasma analysis, and was found to be 6×10 -4 Mass%, 1×10 -3 Mass%, 9×10 -3 Mass%, 9×10 -2 Mass%, 2×10 -1 It was found that carbonate apatite contained 100% silver by mass. Using these products, antibacterial evaluation was performed using the film adhesion method in accordance with JIS-Z2801. The test strain was MRSA, the test medium was 1 / 500 normal bouillon medium, the test conditions were 37°C, relative humidity 90% or higher for 24 hours, and the initial inoculation number was 2.8 × 10 5 CFU mL -1 The bacteria count was measured by counting colonies using the agar plate culture method. After 24 hours, the bacteria count was 8% in the carbonate apatite-coated titanium product that was immersed in a 0.01 mM silver nitrate solution at 25°C for 1 hour, but no bacteria were detectable in the other products. Therefore, carbonate apatite-coated titanium containing silver phosphate has a silver concentration of at least 6 x 10 -4 It was revealed that the antibacterial effect was observed at a concentration of 0.01% by mass or more. The cytotoxicity test was performed using MC3T3-E1 cells as the cell line, culture conditions of 37°C and 5% carbon dioxide gas by volume, culture time of 24 hours, and seeding concentration of 1×10 4 The cell·well and cell numbers were calculated using WST. As a result, it was found that the cell viability of carbonate apatite-coated titanium products immersed in 0.01, 0.1, 1, and 10 mM silver nitrate aqueous solutions at 25°C for 1 hour was 150%, 140%, 65%, and 1%, respectively, compared to the initial cell number. From these results, carbonate apatite-coated titanium was found to have a silver concentration of 6×10 -4 Mass% or more, 1×10 -3 At mass% or less, it exerts antibacterial effects and cell affinity, and at 9×10 -2 It was found that certain cells could survive on carbonate apatite-coated titanium containing a mass percent of silver. The carbonate apatite coverage was 100%, and the carbonate group content of the silver phosphate-containing carbonate apatite was approximately 9.6 mass% regardless of the silver phosphate concentration. The adhesive strength between the carbonate apatite and the roughened titanium substrate was 78.2 ± 4.0 MPa regardless of the silver phosphate concentration, and the main fracture mode was between the roughened titanium and the carbonate apatite layer, with fracture within the carbonate apatite layer also observed. When the carbonate apatite was dissolved in a 1 mol / L nitric acid aqueous solution and the arithmetic surface roughness (Ra) of the roughened titanium substrate was measured, it was 1.9 ± 0.6 μm regardless of the silver phosphate concentration. These results indicate that by immersing carbonate apatite-coated titanium in a silver nitrate solution, it is possible to produce carbonate apatite-coated titanium that exhibits antibacterial properties without affecting the carbonate group content of the carbonate apatite or the adhesive strength with the titanium substrate.

[0035] [Comparative Example 1] The titanium plate used in Example 1 was used without acid etching. The arithmetic surface roughness (Ra) of the titanium plate was 0.7±0.1 μm. Except for that, the same manufacturing method as in Example 1 was used. <Precursor coating process> XRD analysis of the heat-treated product showed that calcite had formed, but was not firmly attached to the titanium substrate. <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting calcite into carbonate apatite, the calcite-coated roughened titanium plate was immersed in a 0.2 molar Na2HPO4 aqueous solution at 80°C. The coating layer peeled off from the titanium plate. Comparison between Example 1 and this Comparative Example revealed that a support having an arithmetic surface roughness of 1.0 μm or more is necessary for producing a carbonate apatite-coated material of the present invention.

[0036] [Example 7] <Rough surface support manufacturing process> A polylactic acid (PLA) plate was crystallized at 110°C for 3 hours, and then etched by immersing in a 1 molar NaOH aqueous solution at 40°C for 24 hours. The arithmetic surface roughness (Ra) of the roughened titanium plate was 4.9±1.7μm. SEM images of the polylactic acid plate before and after etching are shown in Figure 4(a) and Figure 4(b). <Precursor coating process> The rough-surfaced polylactic acid produced was blasted with calcium hydroxide, and excess calcium hydroxide was removed. Next, the calcium hydroxide-coated polylactic acid was exposed to carbon dioxide saturated with 90% by volume of methanol for 24 hours at 4°C. XRD analysis showed that the calcium hydroxide was converted to vaterite. <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting vaterite into carbonate apatite, the vaterite-coated roughened titanium was immersed in a 0.2 molar Na2HPO4 aqueous solution at 20°C for one day. XRD analysis, FT-IR analysis, and elemental analysis showed that vaterite was converted to carbonate apatite. Figure 4(c) shows an SEM image of the produced carbonate apatite-coated polylactic acid. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 10.4 mass%. The adhesive strength between the carbonate apatite and the polylactic acid substrate was 4.6±1.2 MPa, and the fracture mode was mainly between the rough polylactic acid and the carbonate apatite layer, with fracture within the carbonate apatite layer also observed. The carbonate apatite was dissolved in a 0.1 mol / L nitric acid aqueous solution, and the arithmetic surface roughness (Ra) of the rough titanium support was measured to be 5.2±1.9 μm, indicating that the arithmetic surface roughness (Ra) of the rough titanium support was essentially the same even after the precursor coating process and the deficient component addition process were performed. From these results, it was found that the product of the square of the mass percentage of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support was about 500%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0037] [Example 8] <Precursor coating process> The PEEK surface was blasted using α-tricalcium phosphate as the blasting media. It was found that α-tricalcium phosphate, a precursor of carbonate apatite, was embedded in the support surface of the PEEK surface by the blasting treatment. <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting α-tricalcium phosphate into carbonate apatite and to suppress the formation of calcium carbonate, the α-tricalcium phosphate-coated roughened PEEK was immersed in an aqueous solution containing 1.0 molar sodium carbonate and 0.1 molar Na2HPO4 at 80°C for 7 days. XRD analysis, FT-IR analysis, and elemental analysis revealed that α-type tricalcium phosphate had been converted into carbonate apatite. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 11.1 mass%. The adhesive strength between the carbonate apatite and the roughened PEEK was 5.2 MPa, and the main failure mode was between the jig and the adhesive, with failure within the calcium carbonate layer also observed. When the carbonate apatite from the carbonate apatite-coated PEEK was dissolved in 1 molar nitric acid, it was found that the PEEK had been roughened to a surface roughness (Ra) of 3.2 μm. From these results, it is considered that the carbonate apatite coating material has a carbonate group content of 5 mass% or more in the apatite structure and an adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 5.2 MPa, and the product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 640%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0038] [Example 9] <Rough surface support manufacturing process> A soda glass plate was crushed to produce soda glass particles with diameters of 0.105 to 0.125 mm on the surface of the plate, and then heat-treated at 625°C for 24 hours to produce a soda glass plate with an uneven surface. Figure 5(a) shows an SEM image of the glass support thus produced. The measured arithmetic surface roughness (Ra) was 8.7±1.4 μm. <Precursor coating process> A 99.5% by volume ethanol solution of calcium nitrate tetrahydrate with a concentration of 0.5 molar was applied at 5 μL / cm to the roughened glass support. 2 The roughened titanium coated with calcium nitrate was heated to 550°C at 3°C ​​per minute in an electric furnace under a carbon dioxide gas flow of 100 mL per minute, and then heat-treated at 550°C for 5 hours, followed by furnace cooling. XRD analysis showed that calcium carbonate was formed. The SEM image of the calcium carbonate-coated glass substrate is shown in Figure 5(b). <Step of adding missing components> In order to provide the phosphoric acid component that is insufficient in the process of converting calcite to carbonate apatite, the calcium carbonate-coated roughened titanium was immersed in a 1 molar Na2HPO4 aqueous solution at 80°C for three days. XRD, FT-IR and elemental analysis showed that calcite was converted to carbonate apatite. Figure 5(b) shows an SEM image of the carbonate apatite-coated glass substrate. The carbonate apatite coverage was 100%, and the carbonate group content of the carbonate apatite was 10.2% by mass. The adhesive strength between the carbonate apatite and the roughened glass substrate was 4.3±0.7MPa, and the fracture mode was mainly between the roughened glass and the carbonate apatite layer, with fracture within the carbonate apatite layer also observed. The carbonate apatite was dissolved in a 1 molar nitric acid aqueous solution, and the arithmetic surface roughness (Ra) of the roughened glass substrate was measured to be 8.9±1.5μm. It was found that the arithmetic surface roughness (Ra) of the roughened titanium substrate was essentially the same even after the precursor coating process and the deficient component addition process were performed. From these results, it was found that the product of the square of the mass percentage of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support was about 450%. 2 It was found that a carbonate apatite-coated material according to the present invention having a viscosity of 1.0 MPa was produced.

[0039] [Comparative Example 2] The soda glass plate used in Example 9 was used without heat treatment using crushed soda glass. The arithmetic surface roughness (Ra) of the titanium plate was 0.1±0.1 μm. The rest of the manufacturing process was the same as in Example 9. <Precursor coating process> XRD analysis of the heat-treated product showed that calcite had formed, but was not bonded to the soda glass plate. Comparison between Example 9 and this Comparative Example revealed that a support having an arithmetic surface roughness of 1.0 μm or more was required for producing a carbonate apatite-coated material of the present invention.

[0040] [Example 10] The polylactic acid placed in a φ11 mold was softened in an AS ONE dryer (AVO-250N) adjusted to 180°C, and pressure was applied to the mold using a φ10.9 push rod with a 1 kg weight. After 30 minutes, the mold was cooled to produce a polylactic acid plate. Next, carbonate apatite granules (Cytotrans Granule S) manufactured by GC Corporation were placed in a φ11 mold, the polylactic acid disk was placed on top of it, and heated to 180°C in a dryer. After that, pressure was applied with a φ10.9 push rod and a 1 kg weight, and the disk was held for 30 minutes and then cooled. Cytotrans Granule S is carbonate apatite with a minor axis of 0.3 to 0.6 mm, a carbonate group content of 11.6 mass%, and a volume of 5×10 -16 m 3 That's all. Next, the surface was polished to expose the carbonate apatite granules pressed onto the polylactic acid. Figure 6 shows an SEM image of the carbonate apatite-coated polylactic acid after polishing. It was found that the carbonate apatite granules were exposed on the surface of the polylactic acid. Furthermore, observation of the fractured surface revealed that the carbonate apatite granules were embedded in the surface of the polylactic acid plate, which served as the support, and that the polylactic acid plate was covering some of the embedded carbonate apatite granules. Since carbonate apatite does not react during the pressure bonding process, the carbonate group concentration was 11.6 mass% and the carbonate apatite coverage was 69%. The adhesive strength between the carbonate apatite layer and the polylactic acid plate was 22.4 ± 2.5 MPa, and the failure mode was between the epoxy adhesive and the carbonate apatite-coated polylactic acid. The carbonate apatite was dissolved in a 0.1 molar nitric acid solution, and the arithmetic surface roughness (Ra) of the polylactic acid support was measured, which was 13.2 ± 3.6 μm. From these results, the carbonate apatite-coated material of the present invention has a carbonate group content of 5 mass% or more in the apatite structure and an adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 13 MPa, and the product of the mass percent of the carbonate group content in the apatite structure and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support of about 1700%. 2It was found that a carbonate apatite-coated material of the present invention having a compressive strength of 1.0 MPa, at least a part of the carbonate apatite layer is embedded in the surface of a support, and at least a part of the embedded carbonate apatite layer is covered by the support, was produced.

[0041] [Example 11] The polylactic acid plate produced in Example 9 was used as the support. Carbonate apatite powder was produced by immersing calcium carbonate (Karumaru) from Sakai Chemical Industry Co., Ltd. in a 1 molar aqueous solution of disodium hydrogen phosphate at 80° C. for 7 days. The apatite powder was spherical with a diameter of about 5 μm and had a carbonate group concentration of 10.8% by mass. After dissolving the support surface in dichloromethane, carbonate apatite powder was pressed onto the support surface. The dichloromethane on the support surface evaporated in a short time, but the support was further dried at 60°C for 5 hours to completely evaporate the dichloromethane. SEM observation revealed that carbonate apatite granules were exposed on the surface of the polylactic acid plate. Furthermore, observation of the cut surface revealed that carbonate apatite granules were embedded in the surface of the polylactic acid plate, which served as the support, and that the polylactic acid plate covered some of the embedded carbonate apatite granules. The carbonate apatite was dissolved in a 0.1 molar nitric acid solution, and the arithmetic surface roughness (Ra) of the polylactic acid support was measured, which was 3.9 ± 0.6 μm. Since carbonate apatite does not react with dichloromethane, the carbonate group concentration is 10.8 mass%. These results demonstrate that a carbonate apatite-coated material of the present invention was produced in which at least a portion of the carbonate apatite layer was embedded in the surface of the support and at least a portion of the embedded carbonate apatite layer was covered by the support.

[0042] [Comparative Example 3] The same steps as in Example 11 were carried out except that the step of dissolving the polylactic acid plate with dichloromethane was not carried out, but carbonate apatite powder was not embedded in the polylactic acid plate. A comparison between Example 11 and this Comparative Example revealed that a step of dissolving the surface of the polymer support is necessary to produce a carbonate apatite-coated material in which at least a part of the carbonate apatite layer is embedded in the surface of the support and at least a part of the embedded carbonate apatite layer is covered by the support.

Claims

1. A carbonate apatite-coated material comprising a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more, and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass% or more, which covers at least a part of the support, A carbonate apatite-coated material that satisfies at least one of the conditions selected from the group consisting of (A) to (C) below (however, ceramic materials on whose surface carbonate apatite is formed when immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates are excluded from the support). (A) The carbonate group content in the apatite structure is 5 mass % or more, and the adhesive strength between the support and the carbonate apatite layer covering at least a part of the support is 10 MPa or more. (B) The product of the square of the mass percentage of the carbonate group content in the apatite structure and the adhesive strength between the support and a carbonate apatite layer covering at least a portion of the support is 60%2·MPa or more. (C) At least a part of the carbonate apatite layer is embedded in the surface of the support, and at least a part of the embedded carbonate apatite layer is covered by the support.

2. The carbonate apatite coating material according to claim 1, characterized in that the support contains at least one of a material selected from the following group (D) or a polymer or copolymer of a compound selected from the following group (E). (D) Titanium, titanium alloys, stainless steel, cobalt chromium alloys, magnesium alloys, tantalum, polyether ether ketone, polyether ketone, polyarylate, polycarbonate, polyester, polyethylene terephthalate, glass, hydroxyapatite, alumina, zirconia (E) Lactic acid, glycolic acid, ε-caprolactone, glycerol, sebacic acid, hydroxybutyric acid, dioxanone

3. The carbonate apatite coating material according to claim 1 or 2, which contains a drug in the carbonate apatite layer.

4. A carbonate apatite-coated material comprising a support having an arithmetic mean surface roughness (Ra) of 1.0 μm or more and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass % or more covering at least a part of the support (however, ceramic materials on whose surface carbonate apatite is formed when immersed in an aqueous solution selected from the group consisting of phosphates, calcium salts, and carbonates are excluded from the support). ) which comprises the following steps (F) and (G): (F) A step of coating at least a portion of a support having an arithmetic mean surface roughness (Ra) of 1 μm or more with a precursor having a phosphate component and / or a calcium component that becomes carbonate apatite by applying a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component. (G) A step of applying a solution containing at least one component selected from the group consisting of a phosphate component, a calcium component, and a carbonate component to a support at least a portion of which is coated with a carbonate apatite precursor, thereby applying the component to the precursor and converting the precursor into carbonate apatite.

5. A method for producing a carbonate apatite-coated material according to claim 4, comprising at least one of the following steps (H) to (K): (H) applying a solution containing calcium nitrate as an essential component and silver nitrate as an optional component to a support; The nitrate on the surface of the support is thermally decomposed in a gas containing carbon dioxide to produce a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material, or the nitrate is thermally decomposed to produce a calcium oxide-coated material or a silver oxide-containing calcium oxide-coated material, and carbon dioxide is added to produce a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material; A step of applying a solution containing a phosphoric acid component to the calcium carbonate-coated material or the silver oxide-containing calcium carbonate-coated material to produce a carbonate apatite-coated material, or a silver oxide-containing carbonate apatite-coated material, or a silver phosphate-containing calcium carbonate-coated material. (I) applying a solution containing calcium carboxylate as an essential component and silver nitrate as an optional component to a support; Pyrolyzing the compound on the support surface to produce a calcium carbonate-coated material or a silver oxide-containing calcium carbonate-coated material; A step of applying a solution containing a phosphoric acid component to the calcium carbonate-coated material or the silver oxide-containing calcium carbonate-coated material to produce a carbonate apatite-coated material, or a silver oxide-containing carbonate apatite-coated material, or a silver phosphate-containing calcium carbonate-coated material. (J) A step of embedding at least one selected from the group consisting of calcium carbonate, tricalcium phosphate, and tetracalcium phosphate into the surface of a support, and applying a solution containing at least a phosphoric acid component in the case of calcium carbonate, or a solution containing at least a carbonate component in the case of tricalcium phosphate and tetracalcium phosphate, thereby producing a carbonate apatite-coated material. (K) exposing the carbonate apatite-coated material to a solution containing silver ions to produce a silver phosphate-coated carbonate apatite-coated material.

6. After the surface of the polymeric support is softened, dissolved, or melted, A step of pressing either carbonate apatite or carbonate apatite carrying a drug onto a surface of a support; and a chemically synthesized carbonate apatite layer having a carbonate group content of 1 mass% or more covering at least a portion of the support, or a carbonate apatite layer carrying a drug.

Citation Information

Patent Citations

  • Production of bone implant

    JP1987034559A

  • Coating method for bioactive hydroxylapatite film

    JP1990255515A

  • Manufacture of implant

    JP1992371146A

  • Biological implant

    JP2012040194A

  • Gradient coating for biomedical applications

    JP2019150648A